Prevalence of hepatitis B, C, and D virus infection in Haiti: A systematic review and meta-analysis - Vincent, Jeanne Perpétue; Nyamasege, Carolyn; Wang, Su; Madec, Yoann; Shimakawa, Yusuke (Frontiers in Public Health, 2023)
Background: Viral hepatitis causes an important global health burden. In 2016, the World Health Assembly adopted an objective to globally eliminate this as a public health threat by 2030. However, significant gaps exist between countries in their progress. Haiti is the last country that has introduced infant hepatitis B vaccines into the routine immunization program in the Region of the Americas, and its schedule still does not incorporate birth dose vaccines. As the first step to raise awareness of viral hepatitis in this country, we conducted a systematic review and meta-analysis to estimate the prevalence of hepatitis B (HBV), C (HCV), and D (HDV) viruses in Haiti. Methods: We searched PubMed, EMBASE, Web of Science and Scopus for studies reporting the prevalence of HBV, HCV and HDV among Haitian, with no language restriction, published until November 30th 2021. Prevalence was pooled via a random-effects meta-analysis using a generalized linear mixed model with the logit link. The protocol was registered in PROSPERO (CRD42022298081). Results: Of 453 articles retrieved, 25 studies were included: 16 reported the prevalence of hepatitis B surface antigen (HBsAg), three for anti-HCV antibody, and six for both HBsAg and anti-HCV. No study was found for HDV prevalence. The pooled prevalence of HBsAg was 0.7% (95% confidence interval (CI): 0.3-1.4, I2=77.7%) among children, 3.5% (95% CI: 2.8- 4.4, I2=93.2%) in the general adult population and 7.4% (95% CI: 4.0-13.3, I2=83.9%) in high-risk adult population. The pooled prevalence of anti-HCV antibody was 0.9% (95% CI: 0.6-1.4, I2=93.5%) among the general population and 1.4% (95% CI: 0.4-4.2, I2=0.0%) in high-risk adult population. No study reported the prevalence of anti-HCV antibody exclusively in children. Interpretation: The prevalence of blood-borne hepatitis, particularly that of HBV, is substantial in Haiti. The introduction of birth dose hepatitis B vaccines and improving access to testing and treatment services should be urgently considered to meet the elimination goal.